Some Aspects of the Reproductive Biology and Behaviour of the Asiatic Giant Honeybee, Apis Dorsata Fabricius - Nguyen, Quang Tan (1997)
Up to now, little is known about the reproductive biology of the Asiatic wild giant honeybee Apis dorsata. so a comprehensive study on its reproductive biology is needed to improve the beekeeping technique. This study was implemented in the U-Minh Melaleuca forest. Vietnam and the Campus of Universiti Putra Malaysia, Selangor between July 1 995 and January 1997. It was aimed to determine the following: i) The drone t1ight time, sperm number of a sexually-mature drones and age of sexual maturity of drones ii) The number of queen cells and mating nights of v irgin queens. The observation on four colonies of A. dorsata showed that drones started to t1y at 3.4 ± 2.4 (n = 16) minutes after sunsets and stopped after a duration of 24.7 ± 1.0 (n = 16) minutes. The sperm count o f drones during days after emergence indicated that A. dorsata drones became sexually-mature after eightdays- old and a sexually-mature drone had 1.24 ± 0.39 (n = 31) million spermatozoa.